Perencanaan Dan Perancangan Pelabuhan Penumpang Wisata Di Labuhan Lalang, Desa Sumberklampok, Kecamatan Gerokgak, Kabupaten Buleleng - I Gede Yogi Adnyana Puspita Riana; I Nyoman Nuri Arthana; Ni Wayan Nurwasih (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
Tourist port is an area of ​​facilities to support tourist crossing activities to the tourism destination and activities inside the tourism area. Labuhan Lalang is the only official tourist port used for crossing activities to Menjangan Island, Menjangan Island is one of the tourist destinations in Buleleng Regency, with tourism potential namely the underwater diving spots, island land which are the original habitat of Menjangan., also religious tourism areas for Hindus. In fulfilling its function, the port facilities must be obtain comfort and safety when using it, which are problem that occurs in Labuhan Lalang, namely circulation area, main facilities and support for tourist ports, and areas around ports that are currently not meet the national standards. The problems will be resolved by planning and designing using research methods in the form of data collection through theoretical studies, precedents comparision, and interviews with facility users, in hope that the design results in the form of working drawings and 3d images of the area will be able to meet the needs of the facility, standard facilities, as well as visual aspects that have been determined through the data results from the data collection method above.